PPM PENINGKATAN USAHA PUDING SUSU KEDELAI DI KOTA SURABAYA - Rena Febrita Sarie; Nur Jannah; Sayekti Suindyah Dwiningwarni (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
Abstract The community service program in this semester is to develop independent small businesses (SMEs) further from the production of Soy Juice Milk drinks in Sawahan District, Surabaya. The problem faced today is the high price of soybean raw materials which has resulted in a decrease in demand for saridele drinks to partners and the large number of residual soy juice milk that is not sold out in a day. To overcome the problem of limited marketing, we offer to diversify the processed products of soy cider milk drinks into snack products, namely pudding in a wider market segment so that the processed production of Soy Milk can be sold more in the form of food or saridele drinks. Sales that are wider in area will be able to increase the business income of SME partners. In order to maintain the continuity of business operations in the future, better governance of business management is also needed and it is also possible to empower cooperative businesses with other non-entrepreneurial partners. The implementation of this service program includes, among others, 1) Providing training on the production of Saridele Pudding. 2) Assisting in choosing potential markets, promotions and sales locations. 3) Provide assistance in making packaging brands/logos. 4) Provide training and assistance in determining the flavor variants of Soy Milk Pudding. 5) Provide training and assistance in determining production costs. 6) Provide training and assistance in the preparation of financial statements. Keywords: Pudding, Soy Milk, Marketing, Training